2021
DOI: 10.1002/mds.28822
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy Validation of Progressive Supranuclear Palsy‐Predominant Speech/Language Disorder Criteria

Abstract: if it is related to their disease. 9,10 On the contrary, even if all beekeepers diagnosed with PD were among the responders, the estimated prevalence would be 20/1885 × 100 = 1.06% (20 PD patients among 1885 beekeepers aged 60 years and above), which is within the prevalence expected in the general population of the same age. We did not examine participants to confirm the diagnosis of PD. Because in Slovenia all patients with PD are followed up by a neurologist, misdiagnoses are unlikely. Finally, bee stings m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The findings suggest that these brainstem measures could be useful to help differentiate PSP‐Richardson's from PSP‐speech/language. Also notable is that all PSP‐speech/language patients met at least possible PSP criteria 11 ; we did not include patients who only met suggestive of PSP‐speech/language because they have a lower probability of having underlying PSP pathology 58,59 . We have previously shown that patients with suggestive of PSP‐speech/language do not show midbrain atrophy 45 …”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that these brainstem measures could be useful to help differentiate PSP‐Richardson's from PSP‐speech/language. Also notable is that all PSP‐speech/language patients met at least possible PSP criteria 11 ; we did not include patients who only met suggestive of PSP‐speech/language because they have a lower probability of having underlying PSP pathology 58,59 . We have previously shown that patients with suggestive of PSP‐speech/language do not show midbrain atrophy 45 …”
Section: Discussionmentioning
confidence: 99%
“…Early motor speech disorder has specifically been linked to a PSP pathology ( 149 ). A pathology-based study showed that among patients fulfilling the criteria for PSP-SL, those with probable PSP-SL are more likely to have an underlying PSP pathology, while those with suggestive-of-PSP-SL are more consistently associated with a CBD pathology ( 101 ). In a recent study, survival was about 6 years for patients presenting with primary progressive apraxia of speech, around 5 years for agrammatic aphasia, and about 4 years for combined apraxia of speech and agrammatism ( 150 ).…”
Section: Clinical Syndromes With Strong Association To a Primary Tauo...mentioning
confidence: 99%
“…We previously found relative sparing of the SCP in PSP-SL, although that study utilized region-of-interest-based analyses rather than tractography, and the cohort lacked autopsy confirmation ( Whitwell et al, 2021 ). Patients with PSP-SL can also have corticobasal degeneration at autopsy ( Hokelekli et al, 2022 ), and hence it would be reasonable to conclude that the diffusion signal in our previous study was weakened by the inclusion of corticobasal degeneration. Brainstem involvement is greater in speech-language patients with PSP compared to those with corticobasal degeneration ( Josephs et al, 2021 ).…”
Section: Discussionmentioning
confidence: 70%
“…However, no studies have utilized tractography to assess the degree of involvement of the SCP or DRTT in PSP-SL. Furthermore, the pathology underlying PSP-SL is heterogeneous, with PSP pathology only observed in approximately 67% of patients clinically diagnosed with PSP-SL ( Hokelekli et al, 2022 , Josephs et al, 2021 ), and from the Hokelekli study we focus on a subgroup of PSP-SL patients who underwent neuroimaging studies. Hence, autopsy-confirmed cases are needed to assess how SCP and DRTT integrity relates to PSP pathology.…”
Section: Introductionmentioning
confidence: 99%